DAYA SAING MINYAK SAWIT DAN DAMPAK RENEWABLE ENERGY DIRECTIVE (RED) UNI EROPA TERHADAP EKSPOR INDONESIA DI PASAR UNI EROPA - Gisa Rachma Khairunisa; Tanti Novianti (Jurnal Agribisnis Indonesia, 2017)
Palm oil is Indonesia's main export commodity. The EU is Indonesia's largest palm oil importer second after India, so it can affect the condition of Indonesia's palm oil exports. In 2009 the EU issued a Renewable Energy Directive that may have an impact on Indonesia's palm oil exports. The purpose of this study was to analyze the competitive position of Indonesian palm oil using the Revealed Comparative Advantage (RCA) and the Export Product Dynamics (EPD) as well as analyze the impact of policies Renewable Energy Directive towards the export value of Indonesian palm oil using gravity models. RCA analysis results indicate that the Indonesian palm oil has a comparative advantage (RCA> 1). Analysis of Indonesian palm oil EPD average is in position "Rising Star". The results of the analysis of gravity models show a real GDP per capita in the country of destination, the population of the country of destination, the export price of palm oil, and the Renewable Energy Directive policies significantly affect the value of exports of palm oil, while Indonesia and the real exchange rate had no significant effect within the economy.